Efficacy and safety of a fixed combination of insulin degludec/insulin aspart in children and adolescents with type 1 diabetes: A randomized trial. Issue 7 (16th August 2018) - Battelino, Tadej; Deeb, Larry C.; Ekelund, Magnus; Kinduryte, Ona; Klingensmith, Georgeanna J.; Kocova, Mirjana; Kovarenko, Margarita; Shehadeh, Naim
Abstract : Background: Insulin degludec/insulin aspart (IDegAsp) is a fixed soluble co‐formulation of basal and bolus insulin. Objective: To evaluate efficacy and safety of IDegAsp in pediatric patients with type 1 diabetes (T1D). Subjects: Children and adolescents (aged 1 to <18 years) with T1D. Methods: A 16‐week, phase 3b, treat‐to‐target, parallel‐group, open‐label, non‐inferiority trial was conducted at 63 sites in 14 countries from October 2013 to November 2014. Patients were randomized 1:1 (age stratified: 1‐<6 years; 6‐<12 years; 12‐<18 years) to IDegAsp once daily (OD) plus insulin aspart (IAsp) for remaining meals (IDegAsp + IAsp), or IDet OD or twice daily plus mealtime IAsp (IDet + IAsp). The primary end‐point was HbA1c change from baseline at week 16. Results: A total of 362 participants were randomized to IDegAsp + IAsp ( n  = 182) or IDet + IAsp ( n  = 180). HbA1c decreased from baseline to week 16 by 0.3% in both groups (estimated treatment difference: −0.04%‐points [−0.23; 0.15]95%CI (−0.45 mmol/mol [−2.51; 1.60]95%CI ), confirming non‐inferiority. There were no significant differences between treatment groups in fasting or self‐measured plasma glucose. Confirmed hypoglycemia rates did not significantly differ between groups. There was a significant reduction in basal and total insulin dose with IDegAsp + IAsp vs IDet + IAsp (post hoc analysis). Mean number of injections/day was 3.6 and 4.9 with IDegAsp + IAsp and IDet + IAsp, respectively (post hoc analysis). A non‐significant higher rate of severe hypoglycemia was observed with IDegAsp + IAsp vs IDet + IAsp. The most frequent adverse events in both groups were hypoglycemia, headache, and nasopharyngitis. Conclusions: IDegAsp + IAsp was non‐inferior to IDet + IAsp regarding HbA1c, had similar hypoglycemia rates and required fewer injections.